Pengaruh penambahan isolat protein kedelai (IPK) pada adonan tepung beras terhadap sifat sensoris dan kadar protein kwetiau: The effect of adding soybean protein isolate (SPI) to rice flour dough on the sensory properties and protein content of rice noodles (kwetiau) - Karim, Fatimah; Rahmawati, Fitri; Widihastuti, Widihastuti (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
The development of rice noodles (kwetiau) made from rice flour has weaknesses in protein content and texture. Therefore, soy protein isolate (SPI) is used for fortification to overcome protein deficiency and improve organoleptic properties. The study aimed to develop rice noodles from rice flour fortified with SPI to increase protein content and maintain its sensory properties. The method used research and development using 4D models. The research began with the establishment of a reference recipe followed by the formulation of rice noodle dough with the addition of SPI at concentrations of 5%, 7.5%, and 10%. The main ingredients consisted of rice flour, tapioca flour, and SPI produced by Linyi Shansong Biological Products Co. Ltd. The process of making rice noodles includes weighing, mixing, adding water, steaming, cooling, cutting, and vacuum packaging. Observations were made on protein content and sensory properties (color, aroma, taste, texture) through hedonic test of 30 panelists, then analyzed quantitatively. The results showed that the addition of SPI significantly increased the protein content of rice noodles. The 10% SPI formulation increased the protein content from 2.67% (control) to 5.75%. Sensory properties in the addition of 10% SPI had no significant effect on aroma and taste, and even increased panelists' preference for color. However, the texture of rice noodles decreased significantly with the addition of 10% SPI, which was thought to be due to the effect of too high SPI so that the strength and elasticity of the gel decreased. In conclusion, the addition of 10% SPI to rice noodles successfully increased the protein content without affecting the acceptance of aroma, taste, and color. However, formulation optimization needs to be done to improve the decreased texture so that the product can be accepted by consumers as a whole.